De novo design and synthesis of a 30-cistron translation-factor module. Issue 18 (4th September 2017) - Shepherd, Tyson R.; Du, Liping; Liljeruhm, Josefine; Samudyata,; Wang, Jinfan; Sjödin, Marcus O.D.; Wetterhall, Magnus; Yomo, Tetsuya; Forster, Anthony C.
Abstract: Two of the many goals of synthetic biology are synthesizing large biochemical systems and simplifying their assembly. While several genes have been assembled together by modular idempotent cloning, it is unclear if such simplified strategies scale to very large constructs for expression and purification of whole pathways. Here we synthesize from oligodeoxyribonucleotides a completely de-novo -designed, 58-kb multigene DNA. This BioBrick plasmid insert encodes 30 of the 31 translation factors of the PURE translation system, each His-tagged and in separate transcription cistrons. Dividing the insert between three high-copy expression plasmids enables the bulk purification of the aminoacyl-tRNA synthetases and translation factors necessary for affordable, scalable reconstitution of an in vitro transcription and translation system, PURE 3.0.